THE MEDIATING INFLUENCE OF TEAM ALIGNMENT ON MANAGEMENT FUNCTIONS AND PLANT TURNAROUND MAINTENANCE PERFORMANCE - AKBAR, JALAL UD DIN (2017)
Team alignment in plant turnaround maintenance of large process based industry is the focus of the current study. The assets employed by the large process based industry are subjected to planned maintenance management. One of the major activities is plant turnaround maintenance. Large resources that include machines and equipment, materials, and manpower are mobilized during the plant turnaround maintenance. Hence, management and organization of this event is crucial. The best turnaround methodologies do not guarantee turnaround success and high performance due to problems related to team alignment with the turnaround maintenance objectives. Therefore, this study explores team alignment through planning, leading, control and coordination and their influence on turnaround maintenance performance. Data was collected using survey questionnaires. The selection of the companies for the study was based on large process-based companies. Around 96 large process-based companies were identified that performed plant turnaround maintenance in Malaysia. Thirty-nine (39) companies responded and only thirty-one (31) companies’ survey questionnaires were complete and valid for analysis, yielding a response rate of 32%. The findings of the study indicate the significant mediating influence of team alignment on management functions and plant turnaround maintenance performance in Malaysian process-based industries. It indicates that team alignment will not only reduce the conflicts among the teams but will also motivate and encourage the team members to work in teams for achieving turnaround maintenance performance objectives.